PENINGKATAN KEMANDIRIAN EKONOMI PESANTREN BERBASIS PENDIDIKAN EKOPESANTREN DI PONDOK PUTRI 1 AL-AMIEN PRENDUAN SUMENEP MADURA - Nur Rahma Bt Amran (Irfani, 2025)
Islamic boarding schools (pesantren) in Indonesia play a strategic role in shaping the identity of Muslims through education and the dissemination of Islamic values, but they face challenges in achieving economic independence due to their dependence on external funding. To increase economic independence, Islamic boarding schools can leverage existing potential, such as human resources, land, and collaboration with communities or institutions outside the school. An environmentally friendly eco-boarding school program is one solution for creating independent funding sources, as exemplified by the Al-Amien Prenduan 1 Girls' Islamic Boarding School, which manages land for agriculture and livestock farming as an effort to improve welfare and independence. As a pesantren-based educational institution, Al-Amien Prenduan 1 Girls' Islamic Boarding School is expected to be able to manage its natural resources. The purpose of this study is to analyze and develop economic independence at the Al-Amien Prenduan 1 Girls' Islamic Boarding School through eco-boarding school education. The method used in this research is a qualitative approach with a case study approach. Data collection was conducted through interviews, observation, and documentation. The results of the study show that the implementation of eco-boarding school education at Pondok Putri 1 Al-Amien Prenduan can improve the economy of the boarding school, develop the entrepreneurial skills of students, facilitate the development of micro-enterprises, and increase awareness of the importance of economic sustainability through eco-boarding school education.